Beyond Compliance: Harnessing the Power of Internal Public Audits for Sustainability Management Excellence - Gurgu, Elena; Podgroreanu, Radu Ioan; Dragan, Marina (Annals of Spiru Haret University. Economic Series, 2025)
In today's rapidly evolving business landscape, sustainability has emerged as a critical imperative for organizations worldwide. Beyond mere regulatory compliance, sustainability encompasses a holistic approach to environmental, social, and governance (ESG) considerations, aiming for long-term viability and societal impact. Central to this paradigm shift is the role of internal public audits, traditionally viewed as tools for compliance assurance. However, this article argues for a broader reimagining of internal public audits as potent instruments for achieving sustainability management excellence. Drawing upon literature on sustainability, audit practices, and organizational behavior, this article examines the transformative potential of internal public audits in advancing sustainability objectives. It explores how organizations can leverage internal public audits to not only identify compliance gaps but also proactively address sustainability challenges and capitalize on opportunities for innovation and improvement. Key strategies for integrating sustainability considerations into audit processes are discussed, including the incorporation of ESG metrics, stakeholder engagement, and the cultivation of a culture of sustainability within the organization. Furthermore, this article highlights case studies and best practices from leading organizations that have successfully integrated sustainability into their internal public audit frameworks. These examples illustrate the tangible benefits of aligning audit practices with sustainability goals, such as enhanced risk management, improved stakeholder trust, and competitive advantage in the marketplace. By reframing internal public audits as strategic enablers of sustainability management excellence, organizations can unlock new avenues for value creation while fulfilling their broader societal responsibilities. This article provides practical insights and recommendations for organizations seeking to harness the full potential of internal public audits in driving sustainable business practices and achieving long-term success in a rapidly changing world.